Carbonate contourite drifts in the southwest South China Sea: Sedimentary, paleoceanographic and economic implications - Liu, Shan; Liang, Zijun; Zhang, Boda; Su, Haixia; Lei, Zhenyu; Su, Ming (Frontiers in Marine Science, 2022)
Contourite drifts are significant sedimentary features and provide clues for the reconstruction of paleoceanography and paleoenvironment. Although they have been increasingly identified in the world’s ocean, shallow-water contourite drifts (< 300 m depth) remain poorly understood and the examples are rare. This study documents a Middle Miocene shallow-water contourite depositional system in the southwest South China Sea by interpreting seismic reflection data and calibrating results with the previous chronological framework. The depositional system consisted of six mounded drifts and six moats. The contourite features were generated in seismic unit III (16-10.5 Ma) and distributed adjacent to carbonate reefs. They were formed on the proto-continental shelf (50-200 m depth) and shaped by the wind-driven currents. Changes in the sedimentary stacking patterns suggest three evolutionary stages of the contourite features. Stage I represents the growth of the Middle Miocene contourite depositional system between 16 and 10.5 Ma. Stage II marks the termination of carbonate drifts and the burial of the Late Miocene sedimentation during 10.5-5.3 Ma. Stage III started with the development of modern deep-water sedimentary systems since 5.3 Ma. The contourite features are compared with the examples on other South China Sea margins. Significant changes in the paleoceanography occurred at 10.5 Ma and 6.5-5.3 Ma when the dominated bottom currents shifted from the monsoonal wind-driven currents to the North Pacific waters, and then the modern circulation system. The Middle Miocene mounded drifts were likely sourced by the coarse-grained carbonate sands. Fluid flow escaped from the coarse-grained contourite layers and natural gas leakage occurs on the seafloor. Shallow-water carbonate contourite drifts can be served as a good gas reservoir and have great economic potential.